Lagged development and structural imbalances: the relative position of Italy - ALESSANDRINI, P. (PSL Quarterly Review, 2014)
The paper is largely based on the main findings of the research on the state of the utilisation of the labour force in Italy, carried out by a group of economists at the Faculty of Economics and the ISTAO of Ancona, from 1974 to 1978. The study analysed the Italian economy’s lagged level of development by making international comparisons of the structure of productive capacity and income distribution, and their relations with the labour market. In this regard, the structural imbalances of the productive system and the dualism in the labour market between the regular and irregular employment sectors were highlighted. The author provides an overall view of the most important empirical conclusions of the study. JEL: E23, E24